PENGARUH MOTIVASI KERJA DAN IKLIM ORGANISASI TERHADAP KOMITMEN ORGANISASI PADA KARYAWAN TJOKRO HOTEL PEKANBARU - Seriopa Haloho; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Tjokro Pekanbaru Hotel is a company engaged in hospitality services that aims to improve and maximize achievement in its business. For this reason, in order to face competition that is quite difficult, companies must pay attention to work motivation and employee organizational climate in order to create high organizational commitment. But in the company there are still employees who have low commitment, such as the phenomenon of the existence of employees who lack full responsibility for work. For this reason, a study was conducted on how the influence of work motivation and organizational climate on organizational commitment at Tjokro Pekanbaru Hotel. This study aims to analyze work motivation and organizational climate and its effect on organizational commitment to employees of Tjokro Pekanbaru Hotels. Work Motivation as a variable (X1), Organizational Climate as a variable (X2), and Organizational Commitment as a variable (Y). The method in this study is descriptive and quantitative using the SPSS 23 program, 43 samples were used by census methods and data collection techniques through questionnaires. The results of the analysis used the validity test, reliability test, simple linear regression test, determination coefficient test (R2), multiple linear regression test, t test and F test          From the results of data analysis it is known that work motivation has a significant effect on organizational commitment to employees of Tjokro Pekanbaru Hotels, organizational climate has a significant effect on organizational commitment to employees of Tjokro Pekanbaru Hotels, and work motivation and organizational climate have a significant effect on organizational commitment to employees of Tjokro Pekanbaru Hotels. Keywords: Work Motivation, Organizational Climate, and Organizational Commitment